Transformation by v-Src: Ras-MAPK and PI3K-mTOR Mediate Parallel Pathways - Penuel, Elicia (The American Society for Cell Biology, 1999)
An increase in the level of active, GTP-bound Ras is not necessary for transformation of chicken embryo fibroblasts (CEF) by v-Src. This suggests that other Ras-independent pathways contribute to transformation by v-Src. To address the possibility that activation of phosphatidylinositol-3-kinase (PI3K) and the mammalian target of rapamycin (mTOR/FRAP), represents one of these pathways, we have examined the effect of simultaneous inhibition of the Ras-MAPK and PI3K-mTOR pathways on transformation of CEF by v-Src. Transformation was assessed by the standard parameters of morphological alteration, increased hexose uptake, loss of density inhibition, and anchorage-independent growth. Inhibition of the Ras-MAPK pathway by expression of the dominant-negative Ras mutant HRasN17 or by addition of the MAPK kinase (MEK) inhibitor PD98059 reduced several of these parameters but failed to block transformation. Similarly, inhibition of the PI3K-mTOR pathway by addition of the PI3K inhibitor 2-[4-morpholinyl]-8-phenyl-4H-1-benzopyran-4-one (LY294002) or the mTOR inhibitor rapamycin, although reducing several parameters of transformation, also failed to block transformation. However, simultaneous inhibition of signaling by the Ras-MAPK pathway and the PI3K-mTOR pathway essentially blocked transformation. These data indicate that transformation of CEF by v-Src is mediated by two parallel pathways, the Ras-MAPK pathway and the PI-3K-mTOR pathway, which both contribute to transformation. The possibility that simultaneous activation of other pathways is also required is not excluded.